2013
DOI: 10.9790/2380-0445659
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and path analysis studies for yield and quality traits in tomato (Solanum lycopersicum L.)

Abstract: Correlation and path analysis were carried out in nineteen tomato genotypes for yield and quality characters. The association studies showed that fruit yield per plant was positively and significantly correlated with number of fruits per plant and fruit width. However, fruit yield per plant was negatively and significantly correlated with days to last fruit harvest and shelf life. Path analysis studies done to study the cause and effect relationship revealed that plant height, number of fruits per plant, fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 1 publication
(1 reference statement)
8
17
1
Order By: Relevance
“…The path analysis exhibited that individual fruit weight, plant height, ascorbic acid content and days to first fruit maturity had direct positive effect on yield which indicated them as the main contributors for yield (Table 2). Singh et al (2004) and Reddy et al (2013) observed similar results in their investigations. Considering the result of correlation coefficient and path analysis, it can be said that individual fruit weight is the most important factor for improving plant yield.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The path analysis exhibited that individual fruit weight, plant height, ascorbic acid content and days to first fruit maturity had direct positive effect on yield which indicated them as the main contributors for yield (Table 2). Singh et al (2004) and Reddy et al (2013) observed similar results in their investigations. Considering the result of correlation coefficient and path analysis, it can be said that individual fruit weight is the most important factor for improving plant yield.…”
Section: Resultssupporting
confidence: 79%
“…1 & Table 4). Reddy et al (2013) also worked on 19 tomato genotypes and found five clusters by cluster analysis. In the present study, cluster I had maximum number of genotypes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Path analysis differs from simple correlation in that it points out the causes and their relative importance. The above mentioned results are in conformity to findings of Monamodi, et al, (2013), Alirwar et al, (2013), Reddy et al, (2013) and Laxmi et al, (2017).…”
Section: Path Coefficient Analysissupporting
confidence: 82%
“…The results are in accordance with Reddy et al, (2013) for fruit width with fruit yield per plant, number of primary branches per plant and number of flowers per cluster had significantly positive correlation with plant height and days to last fruit harvest and shelf life had significant negative relationship with fruit yield per plant. Similar results are also observed by Alirwar et al, (2013), number of fruits per cluster and ascorbic acid had significantly positive association with number of primary branches per plant and days to 50% flowering while, days to last fruit harvest had negative association with number of primary branches per plant.…”
Section: Correlation Coefficient Analysissupporting
confidence: 75%